The role of ground and microbal biocenosis in sanitary and hygienic of the delta Volga monitoring - B. M. Nasibulina; L. V. Larceva; I. A. Lisickaya; A. A. Istelueva; A. S. Sugralieva (Юг России: экология, развитие)
In the given article the data of the long-term hydrobiological and microbiological monitoring in the hydroecosystem of the Volga delta are shown. The laws of qualitative structure formation, quantitative development of zoobenthos and microbal communities are analysed depending on a kind of antropogeneous process in the persistence of conditionally-factorial researched watercourses. The data about the persistence of conditionally – factorial micro Flore in various eco - niches are submitted. The expediency of realization comp ex of hydro and microbiological monitoring researches is shown at the estimation of pollution water ecology system.